A simple method for expression and purification of Shiga toxin 1 (Stx1) with biological activities by using a single‐promoter vector and native signal peptide. (17th July 2015) - Tu, Wei; Li, Tao; Wang, Qin; Cai, Kun; Gao, Xiang; Wang, Hui
Abstract: The entire stx1 region from Escherichia coli O157:H7, containing two open reading frames ( stx1a and stx1b ), was cloned into pET‐32a with a single promoter. This region was transformed into E. coli TransB (DE3), which is a trxB and gor mutation strain. After expression in the E. coli periplasm in a completely soluble form, the rStx1 was purified and verified by sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS‐PAGE), ELISA, and Western blot analysis. Our rStx1 have Vero cell median cytotoxic dose (CD50 ) and median lethal dose (LD50 ) values of approximately 30 ng and 1.5 µg, respectively. The final yield of the purified rStx1 ranged from 2 to 3 mg/L by one‐step nickel affinity gel column chromatography. This method is an easy approach to the large‐scale preparation of Stx1 at a reasonable cost.